How well do you know your spectators? A study on spectator segmentation based on preference analysis and willingness to pay for tickets. Issue 2 (15th March 2019) - Kaiser, Mario; Ströbel, Tim; Woratschek, Herbert; Durchholz, Christian
ABSTRACT : Research question: Do club managers know enough about their spectators? Fan protests against increasing ticket prices in European sports show the ongoing disconnect between fans and clubs. The purpose of this article is to examine sport event spectators' preferences for tickets and their willingness to pay (WTP) considering innovative ticket features. This research contributes to existing research on spectator segmentation and ticket pricing. Research methods: This study is the first in sport management literature to apply choice-based conjoint analysis in combination with latent classes. We conduct online surveys of two German basketball clubs and collect data on more than 750 spectators. Results and findings: Benefit segmentation analyses of both spectator groups lead to four spectator segments each, which differ depending on preferences for opposing teams, seat categories, and WTP. The results show that the prevailing assumption of homogeneous spectator preferences in sport management research leads to estimation bias. Implications: Spectator preferences are heterogeneous. Therefore, club managers need to know and understand their spectators to better adjust ticket options. Furthermore, the results provide theoretical contributions for spectator segmentation and ticket pricing literature.